Anti-oxidation soldering tin material for semiconductor packaging and preparation method of anti-oxidation soldering tin material
By adding trace amounts of phosphorus and germanium to lead-free solder materials and combining antioxidants, combined with optimized formulas of modified solder alloy powder and flux, the problem of easy oxidation of solder materials at high temperatures is solved, and high oxidation resistance is achieved The performance and low slag yield meet the needs of semiconductor packaging processes.
Patent Information
- Application Number
- CN202411797312.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing lead-free solder materials are prone to oxidation at high temperatures, resulting in a decrease in the quality of the welding process and an increase in the cost of use, making it difficult to meet the dual needs of high strength and good thermal conductivity.
By adding trace amounts of phosphorus and germanium and combining antioxidants, the modified solder alloy powder is modified by silane coupling agent, and combined with rosin, liquid maple fragrance and surfactant in the flux, the antioxidant performance of the solder material is significantly improved. and wettability.
It achieves high oxidation resistance, low slag yield and good wettability of solder materials, meets the strict requirements of the semiconductor packaging process for materials, and reduces the cost of use.
Smart Images

Figure BDA0005177094840000091 
Figure BDA0005177094840000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solder materials, and in particular to an anti-oxidation solder material for semiconductor packaging and a preparation method thereof. Background Art
[0002] Currently, the solder alloys widely used in the semiconductor packaging field primarily include Sn-Pb and Sn-Ag-Cu systems. However, with increasingly stringent environmental protection requirements, lead-free solders are gradually becoming mainstream. However, lead-free solders generally suffer from issues such as high melting points, poor wettability, and poor mechanical properties. This is particularly true for high-frequency, high-speed signal transmission and heat dissipation in high-power devices. Existing lead-free solder materials often struggle to meet the dual requirements of high strength and good thermal conductivity.
[0003] Tin has excellent properties such as softness, low melting point, good ductility, strong plasticity, and non-toxicity. It can be combined with many substances to form alloys with diverse properties and a wide range of applications. Tin-lead solder and lead-free solders, used in processes such as manual dip soldering, wave soldering, automated soldering, and surface mount soldering in the electronics manufacturing industry, account for 70% of tin usage. Due to the significant impact of lead and its compounds on the environment and human health due to their high toxicity, the demand for lead-free solders to replace tin-lead solders is becoming increasingly urgent. However, existing lead-free solders tend to produce tin oxide slag when used at high temperatures, affecting the soldering process and product quality, and increasing their cost. Summary of the Invention
[0004] The purpose of this application is to address the shortcomings of current technology and provide an antioxidant solder material for semiconductor packaging and a preparation method thereof. The antioxidant solder material for semiconductor packaging of this application has high antioxidant performance, low slag production rate, good wettability and non-toxicity. The addition of trace amounts of phosphorus and germanium has no significant effect on the melting temperature of the solder material, but reduces slag production and improves the antioxidant properties of the solder material. Compounding with an antioxidant can significantly improve the antioxidant properties of the solder material. In addition, the preparation method of this application is simple, with high production efficiency and low cost.
[0005] In the first aspect, the present application provides an antioxidant solder material for semiconductor packaging, which adopts the following technical solution: an antioxidant solder material for semiconductor packaging, which includes the following preparation raw materials, calculated by mass: 83-88 parts of modified solder alloy powder, 7-10 parts of flux, and 3-5 parts of composite dispersant, wherein the modified solder alloy powder is prepared by modifying the solder alloy powder with a silane coupling agent.
[0006] By employing the above technical solution, this antioxidant solder material for semiconductor packaging consists of a modified solder alloy powder, a flux, and a composite dispersant. Each component plays a key role in the material's performance: The modified solder alloy powder is modified with a silane coupling agent, improving its dispersibility and compatibility in the flux. This not only enhances the solder material's antioxidant properties, but also reduces slag production and improves wetting properties. The flux is primarily composed of rosin and liquid sweetgum. Rosin exhibits excellent antioxidant properties at high temperatures, rapidly removing oxide films from the solder and base metal surfaces while molten, while also forming a protective film to prevent reoxidation. The liquid sweetgum releases volatile oils at high temperatures, effectively isolating the solder surface from air and further inhibiting oxide film formation. The synergistic effect of these two components significantly enhances the resin's overall antioxidant properties. The composite dispersant optimizes the mixing uniformity of the components, thereby improving the material's overall performance. In summary, the careful combination and modification of these components significantly improve the comprehensive performance of solder materials and meet the strict material requirements of semiconductor packaging processes.
[0007] Preferably, the solder alloy powder comprises the following components in weight percentage: 6-8% zinc, 1-2% nickel, 0.5-1% copper, 0.06-0.08% germanium, 0.01-0.02% phosphorus, and the balance is tin; the particle size of the solder alloy powder is 5-10 μm.
[0008] By adopting the above technical solution, adding a trace amount of phosphorus and germanium has no obvious effect on the melting temperature of the solder material, but reduces the slag production and improves the oxidation resistance of the solder material. Compounding with antioxidants can significantly improve the oxidation resistance of the solder material.
[0009] Preferably, the preparation method of the modified solder alloy powder is as follows: 100-150 parts of solder alloy powder are dispersed in a solution consisting of 200 parts of ethanol and 50 parts of water, and then 2 parts of vinyltriethoxysilane are added thereto. The pH of the solution is adjusted to 4, and the reaction is stirred for 4-5 hours. The modified solder alloy powder is obtained by centrifugation, washing, and drying.
[0010] By adopting the above technical solution, the solder alloy powder is modified by a silane coupling agent, which can significantly improve the dispersibility and compatibility of the solder alloy powder in the flux, thereby improving the oxidation resistance, low slag production rate and wetting performance of the solder material.
[0011] Preferably, the composite dispersant is composed of vinyl bisstearamide, polyacryloyldimethyl ammonium taurate and oleyl alcohol polyoxyethylene ether in a mass ratio of 1:2:1-3.
[0012] By adopting the above technical solution, this composite dispersant improves the dispersibility and compatibility of the solder material in the flux, thereby enhancing the solder material's antioxidant properties, low slag production, and wettability. Vinyl bisstearamide is a commonly used surfactant with excellent emulsifying, dispersing, and wetting properties. In this application, it helps to better disperse the solder alloy powder in the flux, improving the wettability and spreadability of the solder material. Ammonium polyacryloyldimethyltaurate is an anionic surfactant with good water solubility and stability. In this application, it can synergize with vinyl bisstearamide to further improve the dispersibility and compatibility of the solder material in the flux. Oleyl alcohol polyoxyethylene ether is a nonionic surfactant with excellent emulsifying, dispersing, and wetting properties. In this application, it can work together with vinyl bisstearamide and ammonium polyacryloyldimethyltaurate to further improve the dispersibility and compatibility of the solder material in the flux. In summary, the composite dispersant in this application significantly improves the dispersibility and compatibility of the solder material in the flux through the synergistic effect of vinyl bisstearamide, polyacryloyldimethyltaurate ammonium and oleyl alcohol polyoxyethylene ether, thereby improving the antioxidant performance, low slag production rate and wetting performance of the solder material.
[0013] Preferably, the soldering flux comprises the following raw materials in parts by mass: 25-30 parts of rosin, 3-4 parts of liquid sweetgum, 12-15 parts of active agent, 1-2 parts of antioxidant, 2-3 parts of surfactant, 0.5-0.8 parts of corrosion inhibitor, and 38-45 parts of solvent.
[0014] Through the above technical solution, rosin, a natural resin, exhibits excellent oxidation resistance and wettability. At high temperatures, rosin can quickly remove oxide films from the solder and base metal surfaces and form a protective film on the solder material to prevent metal reoxidation. This helps inhibit the formation of oxide films on the solder surface, ensuring that the solder maintains good soldering activity even under continuous high-temperature baking. Liquid sweetgum contains volatile oils that release these volatile oils at high temperatures, effectively isolating the solder surface from air and inhibiting the formation of oxide films. The synergistic effect of liquid sweetgum and rosin enhances the overall antioxidant effect, more effectively removing solder slag and oxide films. The activator has excellent antioxidant properties, significantly reduces slag production, and is less corrosive to solder and welding materials. It also improves the wettability and expansion rate of the solder, helping the solder material to better wet the solder joint and enhance solder quality. Antioxidants are used to further enhance the antioxidant properties of the solder material. By adding trace amounts of elements such as phosphorus and germanium, the oxidation resistance of the solder material can be significantly improved without significantly affecting the melting temperature. Surfactants can reduce the surface tension of solder materials and improve their wettability and expansion rate. This helps the solder material better cover the solder joints and improve the welding quality. Corrosion inhibitors are used to protect solder and welding materials from corrosion and extend their service life. The presence of corrosion inhibitors can reduce the corrosion of solder materials during use and maintain the stability and reliability of solder joints. Solvents are used to dissolve and dilute other components in the flux so that they are evenly distributed and easy to apply. The selection of solvents should take into account their volatility and safety to ensure the safety and environmental friendliness of the flux during use. In summary, the flux in this application, through the combined action of various components, not only has excellent antioxidant properties and low slag production rate, but also has good wettability and non-toxicity. This flux can significantly improve the welding quality and reliability of solder materials and is suitable for high-demand semiconductor packaging applications.
[0015] Preferably, the active agent is composed of dimer fatty acid and succinic acid in a mass ratio of 4:1-3.
[0016] By adopting the above technical solution, dimer fatty acid exhibits excellent wettability, significantly improving the fluidity and coverage of the solder material during the welding process, ensuring sufficient wetting of the solder joint, thereby improving weld quality. Dimer fatty acid can reduce the surface tension of the solder material, making it easier to spread on the welding surface and reducing the generation of slag. Dimer fatty acid has certain antioxidant properties, which can slow the oxidation of the solder under high temperature conditions, extending the service life of the solder material. Succinic acid has an activating effect, quickly removing oxides from the surface of the solder and the base material, ensuring direct contact between the metals during welding and improving weld strength. Succinic acid promotes the melting of the solder material at high temperatures, lowering its melting point and facilitating a smoother welding process. Succinic acid also has certain antioxidant properties, which synergize with dimer fatty acid to further enhance the antioxidant capacity of the solder material. The combined action of dimer fatty acid and succinic acid significantly improves the wettability and fluidity of the solder material, ensuring sufficient wetting of the solder joint and reducing welding defects. The synergistic antioxidant effect of the two effectively slows the oxidation rate of the solder material at high temperatures, reduces the generation of slag, and improves weld quality. By activating the solder joint and promoting fluxing, dimer fatty acids and butyric acid jointly improve the strength and reliability of the solder joint. This combination of active agents not only improves the wettability and oxidation resistance of the solder material, but also enhances its stability and service life at high temperatures. In summary, the combination of dimer fatty acids and butyric acid as active agents plays an important role in the solder material in this application, significantly improving the overall performance of the solder material through synergistic effects, making it suitable for demanding semiconductor packaging applications.
[0017] Preferably, the antioxidant is composed of ethoxyquinoline, tert-butylhydroquinone and butylated hydroxytoluene in a mass ratio of 4:5:1-3.
[0018] By employing the above technical solution, this combination of antioxidants performs multiple functions within the solder material. Ethoxyquinoline, tert-butylhydroquinone, and butylated hydroxytoluene (BHT) exhibit a synergistic effect, collectively enhancing the solder material's antioxidant properties. Ethoxyquinoline is a highly effective antioxidant, effectively capturing free radicals, slowing the oxidation reaction, and extending the lifespan of the solder material. Ethoxyquinoline exhibits excellent thermal stability and maintains its antioxidant properties at high temperatures, making it suitable for high-temperature soldering processes used in semiconductor packaging. Ethoxyquinoline exhibits good compatibility with other ingredients and can be evenly dispersed throughout the solder material to exert its antioxidant properties. Tert-butylhydroquinone (TBHQ) is a powerful free radical scavenger that effectively blocks the propagation of the oxidation reaction chain, protecting the solder material from oxidation. TBHQ maintains its excellent antioxidant properties even at high temperatures, ensuring that the solder material is resistant to oxidation during high-temperature soldering. TBHQ, working in conjunction with other antioxidants, significantly enhances the overall antioxidant effect. Butylated hydroxytoluene (BHT) is also a commonly used antioxidant that works synergistically with ethoxyquinoline and TBHQ to further enhance the antioxidant effect. BHT has good thermal stability and can remain stable under high temperature conditions, making it suitable for high-temperature soldering environments. BHT is compatible with other components in the solder material and does not negatively affect material properties. The combined effects of ethoxyquinoline, tertiary butylhydroquinone, and BHT: 1. Synergistic Antioxidant Effect: These three antioxidants work together to form a powerful antioxidant system that more effectively captures free radicals, slows the oxidation reaction, and significantly improves the antioxidant properties of the solder material. 2. High-Temperature Stability: All three antioxidants maintain excellent stability and antioxidant properties in high-temperature environments, ensuring that the solder material is not easily oxidized during high-temperature soldering. 3. Overall Performance Improvement: Through their synergistic effect, these three antioxidants not only enhance the solder material's antioxidant properties, but also improve its stability and service life at high temperatures. 4. Reduced Slag Production: The presence of these antioxidants reduces oxidation of the solder material during the soldering process, thereby reducing slag production and improving soldering quality and reliability. In summary, the combination of ethoxyquinoline, tert-butylhydroquinone and dibutylhydroxytoluene as antioxidants plays an important role in the solder material in this application. Through synergistic effects, the antioxidant properties and comprehensive performance of the solder material are significantly improved, making it suitable for high-demand semiconductor packaging applications.
[0019] Preferably, the surfactant is composed of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether in a mass ratio of 4:1-3.
[0020] By adopting the above technical solution, the surfactant is composed of fatty alcohol polyoxyethylene ether (AEO) and alkylphenol polyoxyethylene ether (APEO) in a mass ratio of 4:1-3. This surfactant combination plays multiple roles in the solder material, and the fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether have a synergistic effect, which together improves the performance of the solder material. AEO has excellent wetting properties, which can reduce the surface tension between the solder material and the welding surface, improve the wettability of the solder, and ensure more uniform and firm solder joint formation. AEO can help the solder alloy powder better disperse in the flux, prevent powder agglomeration, and thus improve the consistency and reliability of the solder material. AEO can improve the stability of the solder material during storage and use, preventing component separation or precipitation. APEO has excellent emulsifying properties, which can help the oil-soluble components in the auxiliary agent better mix with the water-soluble components to form a stable emulsion, improving the overall effectiveness of the flux. APEO has excellent cleaning ability and can effectively remove oxides and other contaminants on the welding surface, ensuring the cleanliness of the welding surface and improving the welding quality. The combined effects of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether: 1. Synergistic wetting: AEO and APEO work together to significantly improve the wetting properties of the solder material, ensuring that the solder can fully wet the soldering surface during the soldering process to form high-quality solder joints. 2. Enhanced dispersibility: The synergistic effect of these two surfactants can further improve the dispersibility of the solder alloy powder in the flux, avoid powder agglomeration, and improve the uniformity and reliability of the solder material. Stability and compatibility: The synergistic effect of AEO and APEO can enhance the stability of the solder material during storage and use, prevent component separation or precipitation, and ensure the compatibility of the solder material with the soldering surface. 4. Comprehensive cleaning effect: The cleaning ability of APEO combined with the wettability of AEO can more effectively remove oxides and other contaminants on the soldering surface and improve soldering quality. In summary, the combination of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether as a surfactant plays an important role in the tin material in this application. Through synergistic action, it significantly improves the wettability, dispersibility and stability of the solder material, making it suitable for high-demand semiconductor packaging applications.
[0021] Preferably, the corrosion inhibitor is benzotriazole; and the solvent is diethylene glycol monohexyl ether.
[0022] In a second aspect, the present application provides a method for preparing an oxidation-resistant solder material for semiconductor packaging, which adopts the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned antioxidant semiconductor packaging solder material, comprising the following steps: S101. Add a solvent in parts by mass into a container, heat to 120° C., then add rosin, and stir until the rosin is completely dissolved to obtain a rosin solution; S102, lowering the temperature of the rosin solution to 60-65° C. according to the mass fractions, adding liquid sweetgum, an activator, an antioxidant, a surfactant, and a corrosion inhibitor, maintaining the temperature and stirring at a rotation speed of 300-400 rpm for 20-30 minutes to obtain a soldering flux; S103. Add modified solder alloy powder and composite dispersant to the flux in order according to their mass fractions, stir at a speed of 1000-1200 r / min for 30-40 minutes, place in a mold, quickly lower the temperature to 5°C, shape and refrigerate to obtain an antioxidant solder material for semiconductor packaging.
[0023] In summary, the beneficial technical effects of this application are: 1. High oxidation resistance: Modified solder alloy powder is modified with a silane coupling agent, which improves its dispersibility and compatibility in the flux, thereby enhancing the solder material's oxidation resistance. Furthermore, the addition of trace amounts of phosphorus and germanium, along with a compound antioxidant, further enhances the solder material's oxidation resistance.
[0024] 2. Low slag production rate: The addition of trace amounts of phosphorus and germanium significantly reduces the amount of slag produced. At the same time, the activator in the flux also exhibits excellent antioxidant effect, significantly reducing the amount of slag produced.
[0025] 3. Good wettability: The optimized combination of modified solder alloy powder and flux makes the solder material have good wettability, which helps to improve welding quality and reliability.
[0026] 4. Non-toxic and harmless: The materials used are non-toxic and harmless, meet environmental protection requirements, and are suitable for various semiconductor packaging applications.
[0027] 5. Efficient preparation method: The preparation method of the present application is simple, has high production efficiency and low cost, and is suitable for large-scale industrial production. DETAILED DESCRIPTION
[0028] The embodiments of the present application will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, the conditions are carried out according to conventional conditions or manufacturer recommendations. The reagents or instruments used are not specified by the manufacturer and are conventional products that can be purchased commercially.
[0029] In the following examples and preparation examples, 1 part means 100 g.
[0030] Preparation Example 1 Preparation of modified solder alloy powder The solder alloy powder comprises the following components in percentage by weight: 7% zinc, 1.2% nickel, 0.9% copper, 0.07% germanium, 0.015% phosphorus, and the balance being tin; the particle size of the solder alloy powder is 5-10 μm.
[0031] The preparation method of the modified solder alloy powder is as follows: 120 parts of solder alloy powder are dispersed in a solution consisting of 200 parts of ethanol and 50 parts of water, and then 2 parts of vinyltriethoxysilane are added thereto. The pH of the solution is adjusted to 4, and the reaction is stirred for 4.5 hours. The modified solder alloy powder is obtained by centrifugation, washing, and drying.
[0032] Preparation of Comparative Example 1 Solder Alloy Powder The solder alloy powder comprises the following components in percentage by weight: 7% zinc, 1.2% nickel, 0.9% copper, 0.07% germanium, 0.015% phosphorus, and the balance being tin; the particle size of the solder alloy powder is 5-10 μm.
[0033] Preparation of Comparative Example 2: Preparation of Modified Solder Alloy Powder The same as Preparation Example 1, except that: germanium 0%, phosphorus 0%.
[0034] Example 1 An antioxidant solder material for semiconductor packaging comprises the following raw materials, calculated by mass: 83 parts of modified solder alloy powder, 7 parts of flux, and 3 parts of a composite dispersant, wherein the composite dispersant consists of vinyl bisstearamide, ammonium polyacryloyldimethyltaurate, and oleyl alcohol polyoxyethylene ether in a mass ratio of 1:2:1; the flux comprises the following raw materials, calculated by mass: 25 parts of rosin, 3 parts of liquid sweetgum, 12 parts of an active agent, 1 part of an antioxidant, 2 parts of a surfactant, 0.5 parts of benzotriazole, and 38 parts of diethylene glycol monohexyl ether, wherein the active agent consists of dimerized fatty acid and succinic acid in a mass ratio of 4:1, the antioxidant consists of ethoxyquinoline, tert-butylhydroquinone, and butylated hydroxytoluene in a mass ratio of 4:5:1, and the surfactant consists of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether in a mass ratio of 4:1.
[0035] The method for preparing the above-mentioned anti-oxidation solder material for semiconductor packaging comprises the following steps: S101. Add diethylene glycol monohexyl ether in parts by mass into a container, heat to 120° C., then add rosin, and stir until the rosin is completely dissolved to obtain a rosin solution; S102, lowering the temperature of the rosin solution to 60° C. according to the mass fractions, adding liquid sweetgum, an activator, an antioxidant, a surfactant, and benzotriazole, maintaining the temperature and stirring at a speed of 300 r / min for 30 minutes to obtain a soldering flux; S103. Add modified solder alloy powder and composite dispersant to the flux in order according to their mass fractions, stir at a speed of 1000 r / min for 40 minutes, place in a mold, quickly lower the temperature to 5°C, shape and refrigerate to obtain an antioxidant solder material for semiconductor packaging.
[0036] Example 2 An antioxidant solder material for semiconductor packaging comprises the following raw materials, calculated by mass: 88 parts of modified solder alloy powder, 10 parts of flux, and 5 parts of a composite dispersant, wherein the composite dispersant consists of vinyl bisstearamide, ammonium polyacryloyldimethyltaurate, and oleyl alcohol polyoxyethylene ether in a mass ratio of 1:2:3; the flux comprises the following raw materials, calculated by mass: 30 parts of rosin, 4 parts of liquid sweetgum, 15 parts of an active agent, 2 parts of an antioxidant, 3 parts of a surfactant, 0.8 parts of benzotriazole, and 45 parts of diethylene glycol monohexyl ether, wherein the active agent consists of dimerized fatty acid and succinic acid in a mass ratio of 4:3, the antioxidant consists of ethoxyquinoline, tert-butylhydroquinone, and dibutylhydroxytoluene in a mass ratio of 4:5:3, and the surfactant consists of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether in a mass ratio of 4:3.
[0037] The method for preparing the above-mentioned anti-oxidation solder material for semiconductor packaging comprises the following steps: S101. Add diethylene glycol monohexyl ether in parts by mass into a container, heat to 120° C., then add rosin, and stir until the rosin is completely dissolved to obtain a rosin solution; S102, lowering the temperature of the rosin solution to 65° C. according to the mass fractions, adding liquid sweetgum, an activator, an antioxidant, a surfactant, and benzotriazole, maintaining the temperature and stirring at a speed of 400 r / min for 20 minutes to obtain a soldering flux; S103. Add modified solder alloy powder and composite dispersant to the flux in order according to their mass fractions, stir at a speed of 1200 r / min for 30 minutes, place in a mold, quickly lower the temperature to 5°C, shape and refrigerate to obtain an antioxidant solder material for semiconductor packaging.
[0038] Example 3 An antioxidant solder material for semiconductor packaging comprises the following raw materials, calculated by mass: 85 parts of modified solder alloy powder, 9 parts of flux, and 4 parts of a composite dispersant, wherein the composite dispersant consists of vinyl bisstearamide, ammonium polyacryloyldimethyltaurate, and oleyl alcohol polyoxyethylene ether in a mass ratio of 1:2:2; the flux comprises the following raw materials, calculated by mass: 28 parts of rosin, 3.4 parts of liquid sweetgum, 13 parts of an active agent, 1.2 parts of an antioxidant, 2.3 parts of a surfactant, 0.7 part of benzotriazole, and 41 parts of diethylene glycol monohexyl ether, wherein the active agent consists of dimerized fatty acid and succinic acid in a mass ratio of 4:2, the antioxidant consists of ethoxyquinoline, tert-butylhydroquinone, and dibutylhydroxytoluene in a mass ratio of 4:5:2, and the surfactant consists of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether in a mass ratio of 4:2.
[0039] The method for preparing the above-mentioned anti-oxidation solder material for semiconductor packaging comprises the following steps: S101. Add diethylene glycol monohexyl ether in parts by mass into a container, heat to 120° C., then add rosin, and stir until the rosin is completely dissolved to obtain a rosin solution; S102, lowering the temperature of the rosin solution to 63° C. according to the mass fractions, adding liquid sweetgum, an activator, an antioxidant, a surfactant, and benzotriazole, maintaining the temperature and stirring at a speed of 350 r / min for 25 minutes to obtain a soldering flux; S103. Add modified solder alloy powder and composite dispersant to the flux in order according to their mass fractions, stir at a speed of 1100 r / min for 35 minutes, place in a mold, quickly lower the temperature to 5°C, shape and refrigerate to obtain an antioxidant solder material for semiconductor packaging.
[0040] Comparative Example 1 The same as Example 3, except that an equal amount of the solder alloy powder prepared in Comparative Preparation Example 1 is used instead of the modified solder alloy powder.
[0041] Comparative Example 2 The same as Example 3, except that an equal amount of the modified solder alloy powder prepared in Comparative Preparation Example 2 is used instead of the modified solder alloy powder.
[0042] Comparative Example 3 The same as Example 3, except that the composite dispersant is vinyl bisstearamide.
[0043] Comparative Example 4 The same as Example 3, except that the composite dispersant is ammonium polyacryloyldimethyltaurate.
[0044] Comparative Example 5 The same as Example 3, except that the composite dispersant is oleyl alcohol polyoxyethylene ether.
[0045] Comparative Example 6 The same as Example 3, except that the active agent is a dimerized fatty acid.
[0046] Comparative Example 7 The same as Example 3, except that the active agent is succinic acid.
[0047] Comparative Example 8 The same as Example 3, except that the antioxidant is ethoxyquinoline.
[0048] Comparative Example 9 The same as Example 3, except that the antioxidant is tert-butylhydroquinone.
[0049] Comparative Example 10 The same as Example 3, except that the antioxidant is butylated hydroxytoluene.
[0050] Performance Testing The anti-oxidation solder materials for semiconductor packaging prepared in Examples 1 to 3 and Comparative Examples 1 to 10 were sampled and made into welding rods for performance testing. Melting point: The melting temperature of the solder alloy was measured using a Diamondosc differential scanning calorimeter. The sample mass was approximately 10 mg, the test temperature range was 50-450°C, and the heating rate was 10°C / min. Wetting angle: measured using IPC-TM-6502.4.45 test method; Expansion rate determination: Determined using IPC-TM-6502.4.35 test method; Oxidation resistance: The oxidation resistance was tested by static oxidation method. The furnace temperature was 270℃, the mass was 500g, the slag was scraped every 60s, and the slag was taken every 5min. Each group of tests was repeated 3 times, and the average value of the 3 times was taken. Corrosion resistance test: Determined using IPC-TM-6502.6.15 test method.
[0051] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The antioxidant solder materials for semiconductor packaging prepared in Examples 1 to 3 have high antioxidant properties, low slag production rates, good wetting angles, and corrosion resistance.
[0052] 2) A comparative analysis of the performance of the antioxidant solder materials for semiconductor packaging prepared in Example 3 and Comparative Example 1 shows that the solder alloy powder modified by a silane coupling agent can significantly improve the dispersibility and compatibility of the solder alloy powder in the flux, thereby improving the antioxidant performance, low slag production rate and wetting performance of the solder material.
[0053] 3) A comparative analysis of the performance of the antioxidant semiconductor packaging solder materials prepared in Example 3 and Comparative Example 2 shows that the addition of trace amounts of phosphorus and germanium has no significant effect on the melting temperature of the solder material, but reduces the slag production and improves the oxidation resistance of the solder material. Compounding with an antioxidant can significantly improve the oxidation resistance of the solder material.
[0054] 4) A comparative analysis of the performance of the antioxidant semiconductor encapsulation solder materials prepared in Example 3 and Comparative Examples 3-5 shows that the composite dispersant is composed of vinyl bisstearamide, ammonium polyacryloyldimethyltaurate and oleyl alcohol polyoxyethylene ether in a mass ratio of 1:2:2. The combined effect of these components significantly improves the dispersibility and compatibility of the solder material in the flux, thereby improving the antioxidant performance, low slag production rate and wetting performance of the solder material.
[0055] 5) A comparative analysis of the performance of the antioxidant semiconductor encapsulation solder materials prepared in Example 3 and Comparative Examples 6-7 shows that the active agent is composed of dimerized fatty acid and succinic acid in a mass ratio of 4:2. The combined effect of these two components effectively slows the oxidation rate of the solder material at high temperatures, reduces the generation of solder slag, and improves the welding quality. By activating the solder joint and promoting fluxing, the dimerized fatty acid and butyric acid jointly improve the strength and reliability of the welded joint. This combination of active agents not only improves the wettability and oxidation resistance of the solder material, but also enhances its stability and service life at high temperatures, significantly improving the overall performance of the solder material, making it suitable for demanding semiconductor packaging applications.
[0056] 6) A comparative analysis of the performance of the antioxidant solder materials for semiconductor packaging prepared in Example 3 and Comparative Examples 8-10 shows that the antioxidant is composed of ethoxyquinoline, tert-butylhydroquinone and dibutylhydroxytoluene in a mass ratio of 4:5:2. The combined effect of these components significantly improves the antioxidant performance and overall performance of the solder material, making it suitable for demanding semiconductor packaging applications.
[0057] The above embodiments are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the above embodiments provide a detailed description of the present application, relevant technical personnel should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. An anti-oxidation solder material for semiconductor packaging, characterized in that: The preparation raw materials include the following by weight: 83-88 parts of modified solder alloy powder, 7-10 parts of flux, and 3-5 parts of composite dispersant, wherein the modified solder alloy powder is prepared by modifying the solder alloy powder by a silane coupling agent.
2. The anti-oxidation solder material for semiconductor packaging according to claim 1, characterized in that: The solder alloy powder comprises the following components in weight percentage: 6-8% zinc, 1-2% nickel, 0.5-1% copper, 0.06-0.08% germanium, 0.01-0.02% phosphorus, and the balance is tin; the particle size of the solder alloy powder is 510 μm.
3. The anti-oxidation solder material for semiconductor packaging according to claim 1, characterized in that: The preparation method of the modified solder alloy powder is as follows: according to the mass fraction, 100-150 parts of solder alloy powder are dispersed in a solution consisting of 200 parts of ethanol and 50 parts of water, and then 2 parts of vinyl triethoxysilane are added thereto, the pH of the solution is adjusted to 4, the reaction is stirred for 4-5 hours, and the modified solder alloy powder is obtained by centrifugation, washing and drying.
4. The anti-oxidation solder material for semiconductor packaging according to claim 1, characterized in that: The composite dispersant is composed of vinyl bisstearamide, ammonium polyacryloyl dimethyl taurate and oleyl alcohol polyoxyethylene ether in a mass ratio of 1:2:1-3.
5. The anti-oxidation solder material for semiconductor packaging according to claim 1, characterized in that: The soldering flux comprises the following raw materials, calculated by weight: 25-30 parts of rosin, 3-4 parts of liquid maple, 12-15 parts of activator, 1-2 parts of antioxidant, 2-3 parts of surfactant, 0.5-0.8 parts of corrosion inhibitor and 38-45 parts of solvent.
6. The anti-oxidation solder material for semiconductor packaging according to claim 5, characterized in that: The active agent is composed of dimer fatty acid and succinic acid in a mass ratio of 4:1-3.
7. The anti-oxidation solder material for semiconductor packaging according to claim 5, characterized in that: The antioxidant is composed of ethoxyquinoline, tert-butylhydroquinone and butylated hydroxytoluene in a mass ratio of 4:5:1-3.
8. The anti-oxidation solder material for semiconductor packaging according to claim 5, characterized in that: The surfactant is composed of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether in a mass ratio of 4: 1-3.
9. The anti-oxidation solder material for semiconductor packaging according to claim 5, characterized in that: The corrosion inhibitor is benzotriazole; and the solvent is diethylene glycol monohexyl ether.
10. A method for preparing an oxidation-resistant solder material for semiconductor packaging according to any one of claims 1 to 9, characterized in that: The following steps are involved: S101, adding a solvent into a container according to the mass fraction, heating to 120° C., then adding rosin, and stirring until the rosin is completely dissolved to obtain a rosin solution; S102, according to the mass fraction, lowering the temperature of the rosin solution to 60-65° C., adding liquid sweetgum, an activator, an antioxidant, a surfactant and a corrosion inhibitor, maintaining the temperature and stirring at a rotation speed of 300-400 r / min for 20-30 minutes to obtain a soldering flux; S103. Add modified solder alloy powder and composite dispersant to the flux in order according to their mass fractions, stir at a rotation speed of 1000-1200 r / min for 30-40 min, place in a mold, quickly lower the temperature to 5°C, shape and refrigerate, and obtain an antioxidant solder material for semiconductor packaging.
Citation Information
Patent Citations
Modified tin powder, preparation method thereof and tin paste
CN115609184A
Tin-indium alloy solder and preparation method thereof
CN118385811A
Functional polymer, preparation method and application thereof, tin powder modification method and tin paste
CN118496435A
High-oxidation-resistance lead-free solder paste and preparation method thereof
CN118808986A
Surface processing agent for tin or tin alloy material
US20070131141A1